Increasing Artificial Intelligence Literacy (AI) Through Digital Training for Teachers SMPN 2 Kabupaten OKU Timur - Fatimah, Siti; Lestari, Inda; Lestari, Cyndi; Husniyah, Dini Milatul; Larita, Nadia Putri; Firdaus, Thoha (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
This training aims to enhance artificial intelligence (AI) literacy among junior high school teachers at SMP Negeri 2 OKU Timur through a participatory and hands-on approach. The program was motivated by the low level of understanding and utilization of AI technology in schools, especially in non-urban areas. The implementation method included needs assessment, material delivery, practical use of AIPRM-GPT, Gamma, and inVideo applications, and evaluation through pretest and posttest. The results showed an increase in participants' understanding of AI concepts and applications, as indicated by an improvement in scores from an average of 2.7–3.7 to 3.2–4.0. The training also provided reflective and collaborative experiences for both participants and the implementation team. The implications of this activity indicate that AI training can drive digital transformation in schools and enhance the competencies of teachers and students as change agents.